Training on financia statement preparation to enhance accountability in Village-Owned Enterprises (BUMDes) in Rokan Hulu Regency - Agung Dinarjito; Azas Mabrur; Hari Sugiyanto (Pengmasku, 2026)
This community service program aims to enhance the capacity of Village-Owned Enterprise (BUMDes) managers in Rokan Hulu Regency in preparing financial statements in accordance with the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration (Kepmendesa PDTT No. 136 of 2022). The main challenges faced by the partners include limited competencies in transaction recording, the preparation of financial statements in line with applicable accounting standards, and the use of non-integrated applications. The program was conducted from August to November 2024 using a Training of Trainers (ToT) approach, technical assistance, and both offline and online mentoring. The methods applied included needs assessment, knowledge sharing sessions, simulations of financial statement preparation using the Microsoft Excel-based PPAK BUMDes Application version 3.8, and hands-on assistance in preparing both unit-level and consolidated financial reports. The results demonstrate a significant improvement in participants’ understanding, with 23 out of 29 participants able to accurately prepare financial statements. The participating BUMDes are now capable of generating income statements, statements of changes in equity, balance sheets, and cash flow statements automatically through the application. Challenges related to initial balance input and profit allocation were successfully addressed through continuous consultation. Overall, this program contributes to improving accountability and transparency in BUMDes financial management and shows strong potential for replication in other regions.